Human investigations into the arterial and cardiopulmonary baroreflexes during exercise - Fadel, P. J.; Raven, P. B. (Experimental Physiology, 2012)
After considerable debate and key experimental evidence, the importance of the arterial baroreflex in contributing to and maintaining the appropriate neural cardiovascular adjustments to exercise is now well accepted. Indeed, the arterial baroreflex resets during exercise in an intensity-dependent manner to continue to regulate blood pressure as effectively as at rest. Studies have indicated that the exercise resetting of the arterial baroreflex is mediated by both the feedforward mechanism of central command and the feedback mechanism associated with skeletal muscle afferents (the exercise pressor reflex). Another perhaps less appreciated neural mechanism involved in evoking and maintaining neural cardiovascular responses to exercise is the cardiopulmonary baroreflex. The limited information available regarding the cardiopulmonary baroreflex during exercise provides evidence for a role in mediating sympathetic nerve activity and blood pressure responses. In addition, recent investigations have demonstrated an interaction between cardiopulmonary baroreceptors and the arterial baroreflex during dynamic exercise, which contributes to the magnitude of exercise-induced increases in blood pressure as well as the resetting of the arterial baroreflex. Furthermore, neural inputs from the cardiopulmonary baroreceptors appear to play an important role in establishing the operating point of the arterial baroreflex. This symposium review highlights recent studies in these important areas indicating that the interactions of four neural mechanisms (central command, the exercise pressor reflex, the arterial baroreflex and cardiopulmonary baroreflex) are integral in mediating the neural cardiovascular adjustments to exercise.